Implementation of the Use of the Hospital Management Information System (SIMRS) at the PKU Muhammadiyah Clinic, North Lombok - Pranata, Andi (Business Management, 2024)
The advancement and development of information technology is currently growing so rapidly in all fields including in the health sector. Especially in hospitals. Hospital information systems have an important role in clinical and administrative services. One of the developments in information systems in hospitals is electronic medical records which have become an integral part of the online-based Hospital Management Information System (SIMRS) application which is computerized in an integrated system stored in a central database.